More than Just Antioxidants: Redox-Active Components and Mechanisms Shaping Redox Signalling Network - Monika Kuczyńska; Patrycja Jakubek; Agnieszka Bartoszek (MDPI AG, 2022)
The concept of oxidative stress as a condition underlying a multitude of human diseases has led to immense interest in the search for antioxidant-based remedies. The simple and intuitive story of "the bad" reactive oxygen species (ROS) and "the good" antioxidants quickly (and unsurprisingly) lead to the commercial success of products tagged "beneficial to health" based solely on the presence of antioxidants. The commercial success of antioxidants by far preceded the research aimed at understanding the exact redox-related mechanisms that are in control of shaping the states of health and disease. This review describes the redox network formed by the interplay of ROS with cellular molecules and the resulting regulation of processes at the genomic and proteomic levels. Key players of this network are presented, both involved in redox signalling and control of cellular metabolism linked to most, if not all, physiological processes. In particular, this review focuses on the concept of reductive stress, which still remains less well-established compared to oxidative stress.